Connecting dots : a blind life - Miele, Joshua Alexander; Jamieson, Wendell (Grand Central Publishing, 2025)
"When Joshua Miele was four years old, he answered his front door, and a mentally disturbed neighbor poured a cup of acid over his head, horrifically burning him and blinding him for life. It was a tragedy that could've destroyed him, but instead, Miele-naturally curious, and a born engineer-not only recovered, but flourished, finding increasingly inventive ways not only to help himself thrive in a world built for the sighted, but to help others to do the same. In "Connecting Dots" -a reference to braille and a metaphor for Miele's explorations and discoveries-readers are treated to a memoir that is as illuminating as it is entertaining, and ultimately as triumphant as they come: in 2022, Miele fulfilled a nearly lifelong dream when he won a MacArthur genius Grant. "Connecting Dots" comes at a time when disability is finally starting to get the recognition (and legislation) that it deserves, and entering the popular culture in a huge way, from Coda to Crip Camp and beyond. We are at an inflection point in addressing those who have historically been marginalized-a conversation that must include those with disabilities. This is the moment for a book like this in so many ways, and Miele is, apart from the obvious reasons, the perfect person to write it. He is funny, pragmatic, and direct-with a healthy dose of attitude. In telling his own story-spanning from the 1970s to today-he also speaks to how the world has changed (and how it hasn't) when it comes to blindness, and to disability and accessibility more broadly. Miele has always considered his challenges to be opportunities, and that is something we can all learn from"--